2020
DOI: 10.1200/jco.19.02503
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase IIB Trial of Proton Beam Therapy Versus Intensity-Modulated Radiation Therapy for Locally Advanced Esophageal Cancer

Abstract: PURPOSE Whether dosimetric advantages of proton beam therapy (PBT) translate to improved clinical outcomes compared with intensity-modulated radiation therapy (IMRT) remains unclear. This randomized trial compared total toxicity burden (TTB) and progression-free survival (PFS) between these modalities for esophageal cancer. METHODS This phase IIB trial randomly assigned patients to PBT or IMRT (50.4 Gy), stratified for histology, resectability, induction chemotherapy, and stage. The prespecified coprimary end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
184
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 26 publications
4
184
0
3
Order By: Relevance
“…Longer survival than SBRT, spares more normal liver cells from radiation damage than treating with conventional RT [39][40][41] Esophageal Proton vs. IMRT Randomized Phase II The mean total toxicity burden was considerably lower with protons than with IMRT [42] Brain (Adult) Proton Trial study unknown Significantly reduced the side effects and better neurocognition over time after treatment [43][44][45][46] Brain (Pediatric) Proton vs. Photon Trial study unknown Spared more surrounding normal tissue; reduced side effects and increased five-year survival rates (72-100%) [32,[47][48][49][50] Safer to deliver high dose of radiation and better neurocognition [44][45][46]51] 2.3.2. Carbon Ion Therapy 12 C ions are the optimal ion for treating deep-seated tumors, because the higher relative biological effectiveness (RBE) resulting from variations in linear energy transfer (LET) along the ion path can be limited to the tumor volume with minimal normal tissue injury along the entrance track.…”
Section: Proton Therapymentioning
confidence: 99%
“…Longer survival than SBRT, spares more normal liver cells from radiation damage than treating with conventional RT [39][40][41] Esophageal Proton vs. IMRT Randomized Phase II The mean total toxicity burden was considerably lower with protons than with IMRT [42] Brain (Adult) Proton Trial study unknown Significantly reduced the side effects and better neurocognition over time after treatment [43][44][45][46] Brain (Pediatric) Proton vs. Photon Trial study unknown Spared more surrounding normal tissue; reduced side effects and increased five-year survival rates (72-100%) [32,[47][48][49][50] Safer to deliver high dose of radiation and better neurocognition [44][45][46]51] 2.3.2. Carbon Ion Therapy 12 C ions are the optimal ion for treating deep-seated tumors, because the higher relative biological effectiveness (RBE) resulting from variations in linear energy transfer (LET) along the ion path can be limited to the tumor volume with minimal normal tissue injury along the entrance track.…”
Section: Proton Therapymentioning
confidence: 99%
“…Generated IMPT plans are then verified by plan evaluation on maximum exhalation and maximum inhalation respiratory phases, as well as a separate interplay effect calculation. 45 Previous dosimetric studies [56][57][58][59] of esophageal carcinoma treatment compared both proton and photon treatments. Zhang et al reported that proton therapy provided significantly better sparing of the lungs than IMRT.…”
mentioning
confidence: 99%
“…34 Most recently, Lin et al reported the result of a phase IIB trial that for locally advanced esophageal cancer, proton beam therapy (PBT) reduced the risk and severity of adverse events (AEs) while maintaining similar progression-free survival (PFS) when compared with IMRT. 59 Specifically for IMPT, different configurations may lead to different outcomes, such as spot sizing and spacing. 38 The selection of beam angles is important as well.…”
mentioning
confidence: 99%
“…Numerous dosimetric studies have illustrated superior cardiopulmonary dose sparing with PBT compared with both 3DCRT and IMRT ( 29 32 ). A newly reported randomized phase IIB trial compared total toxicity burden (TTB) and PFS between PBT and IMRT for esophageal cancer ( 33 ). The results suggested that PBT for neoadjuvant or definitive treatment of locally advanced EC produced a lower toxicity profile and fewer postoperative complications, thus leading to a lower TTB, but similar PFS, compared to IMRT.…”
Section: Discussionmentioning
confidence: 99%